Nuclear Data Sheets for A=160 - Nica, N. (Nuclear data sheets, 2021)
The experimental results published before May 2021 from the various reaction and decay studies leading to nuclides of Z=59 to Z=75, 160Pr, 160Nd, 160Pm, 160Sm, 160Eu, 160Gd, 160Tb, 160Dy, 160Ho, 160Er, 160Tm, 160Yb, 160Lu, 160Hf, 160Ta, 160W, 160Re in the A=160 mass chain have been reviewed. These data are summarized and presented, together with adopted level schemes and properties. This work is intended to supersede the previous evaluation of the A=160 nuclides by C.W.Reich (2005Re18), which was published in Nuclear Data Sheets 105, 557 (2005).